Papers of James McInnes Sinclair - Sinclair, James M. (James McInnes) (1880)
Copies of letters written while James Sinclair was Victoria's Commercial Agent in the Far East (1906-1911), transcript of his diary kept on voyage overseas (1894), transcript of diary kept by his wife on a voyage to London (1895-1896), transcript of a diary he kept of a journey to the Riverina district (1880), his memoirs written in 1930 entitled: Retrospect and an article about him (4 p.).
Photocopies.
Manuscript reference no. : MS 5052.
Guide to collections of manuscripts relating to Australia
Originals in private ownership.
Born on the goldfields of Victoria, James McInnes Sinclair (1855-1934) owned and managed various grazing properties in northern Victoria. In 1895 he was appointed Commercial Agent for the Government of Victoria in London; from 1906 to 1911 he was responsible for extending trade in the Far East.
Keywords: Sinclair, James M. -- Archives; Farmers -- Victoria -- Archives; Victoria -- Officials and employees -- Archives; Public servants; Graziers